Analysis of Combustion Characteristics in Boilers Using Comparison of Coal Fuel Mixtures and Bark Biomass To Determine Optimal Combustion Conditions in a Steam Power Plant - Tikkos Sihombing; Awaludin Martin (Universitas Negeri Padang, 2023)
Currently, several material production industries have used self-sustaining power generation systems. Where the most common steam power plant system is found as an option to be used as a source of electricity. The use of biomass as an additional material for fuel in power plant has been widely carried out. This method is more commonly known as cofiring. Analysis of the cofiring combustion system of biomass in the boiler needs to be carried out in order to determine the characteristics of the combustion system that occurs. By varying the composition of the fuel, an analysis of the energy produced from the combustion reaction will be calculated. In this study, the comparison of the use of coal and wood bark was varied at conditions 80:20, 70:30, 60:40, 50:50, 40:60, 30:70, 20:80. Assuming that the steam rate and temperature conditions to be achieved from the combustion products are constant. From the results of the analysis it was found that an increase in the amount of cofiring bark resulted in a decrease in the heating value of the combustion reaction and an increase in fuel capacity. Thus, it can be concluded that the use of bark cofiring in boilers with a coal design is less effective because it will require additional energy to increase the fuel consumption rate and reduce combustion efficiency due to not achieving optimal combustion energy because the initial design combustion chamber capacity is fixed.